Endogenous Glycosaminoglycans in Various Pathologic Plasma Samples as Measured by a Fluorescent Quenching Method. (December 2022) - Kantarcioglu, Bulent; Mehrotra, Siddharth; Papineni, Charulatha; Siddiqui, Fakiha; Kouta, Ahmed; Hoppensteadt, Debra; Bansal, Vinod; Darki, Amir; Van Thiel, David H.; Fareed, Jawed
Endogenous glycosaminoglycans (GAGs) with a similar structure to heparin are widely distributed in various tissues. A fluorescence probe, namely Heparin Red, can detect polyanionic GAGs in plasma samples. The purpose of this study is to measure endogenous GAGs in various plasma samples obtained from different pathologic states in comparison to healthy controls utilizing this method. Plasma samples were obtained from patient groups including atrial fibrillation (AF), end-stage-renal-disease (ESRD), diabetes mellitus (DM), sepsis, cancer, liver disease (LD), and pulmonary embolism (PE). Normal human plasma (NHP) was used as healthy controls. The Heparin Red kit from Red Probes (Münster, Germany) was used for the quantification of endogenous GAGs in each sample before and after heparinase I degradation. All results were compiled as group means  ±  SD for comparison. NHP was found to have relatively low levels of endogenous GAGs with a mean concentration of 0.06 μg/mL. The AF, ESRD, DM, and sepsis patient samples had a mean endogenous GAG concentration of 0.55, 0.72, 0.92, and 0.94 μg/mL, respectively. The levels of endogenous GAGs were highest in cancer, LD, and PE patient plasma samples with a mean concentration of 1.95, 2.78, and 2.83 μg/mL, respectively. Heparinase I degradation resulted in a decline in GAG levels in plasma samples. These results clearly show that detectable Heparin Red sensitive endogenous GAGs are present in circulating plasma at varying levels in various patient groups. Additional studies are necessary to understand this complex pathophysiology.